Electrical Energy Audit in Pratama Tapan Hospital - Putra, Nanda Okta; Aini, Zulfatri; Putri, Dila Marta (Jurnal Edukasi Elektro, 2024)
Hospitals, as large energy consumers, must adopt efficient energy-saving measures due to cost increases, regulations, and climate change concerns. In this study, an electrical energy audit was conducted at Pratama Tapan Hospital to identify energy-saving opportunities and recommend equipment replacements or technology upgrades. The primary objective was to determine the Energy Consumption Intensity (ECI) and analyze the potential for energy savings. The audit re-vealed an ECI value of 10.33 kWh/m²/year, highly efficient by ASEAN-USAID standards. However, 100% of rooms didn't meet the SNI 03-6197-2000 light intensity standard, causing discomfort. The study recommends installing specific light fixtures and adjusting lamp power to comply with the standard. These findings offer valuable insights for healthcare institutions striv-ing to achieve sustainability goals.